Rocky (1976) [videorecording (DVD)] - Avildsen, John G., 1936-; Stallone, Sylvester; Shire, Talia; Meredith, Burgess, 1907-1997 (MGM Home Entertainment, 2005)
Stallone stars as an unknown boxer from the slums of Philadelphia who is given a once-in-a-lifetime shot at the world heavyweight title.